Procedural challenges in the mode of commencement of fundamental right suit under the fundamental rights (enforcement procedure) rules 2009 (2021)
Under the Nigerian law, human rights are categorized \-s into justiciable and non-justiciable rights and they are contained in Chapters 4 and 2 of the Constitution of the Federal Republic of Nigeria 1999 as amended. In enforcing the justiciable rights, Section 46(3) of the 1999 CFRN, empowers the Chief Justice of Nigeria (CJN) to make Rules for their enforcement. Hence, the CJN made the Fundamental Rights (Enforcement Procedure) Rules, 2009 (FREPR 2009). This paper examines the mode of commencement of an action under the FREPR 2009. It adopts a doctrinal methodology by engaging in textual analysis of FREPR 2009. It finds that under Order II Rule 2 of the FREPR 2009, an application for the enforcement of fundamental rights may be made by any originating process accepted by the court which are writ of summons, petition, originating motion and originating summons. Therefore, it is argued that this provision has created a situation of uncertainty in respect of the mode of commencement of an action. It is recommended that FREPR 2009 be amended to make certain the mode of commencement and that originating motion is preferable.